Industry FDI and the Distribution of Plant Productivity: Analysis Using Korean Plant‐Level Data. (June 2017) - Choi, Bo‐Young; Pyun, Ju Hyun
Abstract : We examine the effects of inward FDI on the distribution of plant total factor productivity. Using Korean manufacturing plant‐level data covering 1990–2007, we find that industry FDI had heterogeneous effects on plant productivity and its distribution in terms of industry characteristics, such as industry concentration index and capital intensity. While sectoral FDI drove up productivity more for plants in industries with low concentration, it had negative effects on productivity especially for the least productive plants in industries with high concentration and high capital intensity. Our results also reveal that the positive effect of FDI was greater for exporters than for non‐exporters.